Themes and theories of the Insider Trading. The 2004 Security Services Act - Adams, Morgan Ross (Department of Commercial Law, 2014)
According to Blackman et al, 'insider trading' initially referred 'to the sale and purchase of a company's shares, debentures or other securities by persons connected or associated with the company (the 'insiders'), who are in possession of confidential, 'price-sensitive' information gained as a result of that association and not available to (other) shareholders or to the general public.' The practice of insider trading was first made illegal in South Africa with the introduction of s 233 of the Companies Act 61 of 1973. By the criminalising of insider trading, the conduct of an insider trader has been classified as a wrong against society. At present, the relevant provisions of the Securities Services Act of 2004 regulate such practices. The Act has repealed the Insider Trading Act 135 of 1998, which had previously governed criminal and civil liability in terms of the offence. The insider trading provisions of the Act form part of corporate governance regulations, which are aimed at improving the efficiency of financial markets. This dissertation focuses on the significant transformation that South Africa's insider trading laws have gone through since this practice was first outlawed in 1973. It aims to tease out and discuss some of the core themes of the Act, and in doing so, note the various consistencies that exist between these themes and those of South Africa's previous insider trading laws. A similarly important aim will be to determine whether the Act represents a different emphasis in regard to what has previously constituted the 'wrong' of insider trading. In addition, the relevant flaws and inadequacies of the Act that appear to have resulted from the legislature's attempt to 'toughen' up on the previous provisions as well as certain evidential problems will be discussed. It will be shown that, despite the fact that there has been a general trend to broaden the offences as well as certain key definitions, notably that of an 'insider', so that the link between the Act and the previous enactments is not as obvious as it use to be, it is submitted that this link has not completely broken down.